India and Japan: Emerging Indo-Pacific Security Partnership - Jaishankar, Dhruva (2016)
India and Japan, motivated primarily by shared concerns about China, have been developing a closer defence partnership defined by regular maritime exercises and high-level political consultations. The upward trajectory in strategic ties since 2006 can be maintained, as long as both countries take certain structural limitations into consideration.